A rare and emerging pathogen: Raoultella planticola identification based on 16S rRNA in an infant. Issue 1 (January 2018) - Atıcı, Serkan; Alp Ünkar, Zeynep; Öcal Demir, Sevliya; Akkoç, Gülşen; Yakut, Nurhayat; Yılmaz, Şerife; Erdem, Kübra; Çınar Memişoğlu, Aslı; Ülger, Nurver; Soysal, Ahmet; Özek, Eren; Bakır, Mustafa
Abstract: Raoultella planticola is rarely associated with clinical infection, and a limited number of pediatric cases have been reported. Herein we report a case of bacteremia presumptively secondary to bilateral conjunctivitis in an infant caused by R. planticola which was successfully treated with piperacillin-tazobactam. It should be kept in mind that R. planticola can be a pathogen in pediatric age groups.